Bone marrow transplantation data for Marmara University School of Medicine: 1989-1998 - (:unkn) unknown (My University, 1998)
Objectives: The aim of this study was to analyse the bone marrow transplantation data at the Haematology Department of Marmara University Hospital between 1989 and 1998. Methods: The transplant data and survival of 56 patients, who had allogeneic (n = 42) or autologous (n = 14) bone marrow transplantation, were evaluated retrospectively. Results: The most common complications encountered in bone marrow transplant patients were infections and graft versus host disease (GVHD). The primary causes of death were acute and chronic GVHD. Chronic GVHD was significantly higher in the allogeneic peripheral stem cell transplantation (Allo-PBSCT) in comparison with allogeneic bone marrow transplantation (Allo-BMT). Disease free survival for allo-BMT, allo-PBSCT, and autologous PBSCT was 61.2%, 54.5% and 30.7% respectively. Transplant related mortality in allo-BMT, and allo-PBSCT was 32.2%, and 36.3% respectively. Disease free survival in acute myeloid leukaemia and acute lymphocytic leukaemia patients were 70.5% and 66.6% respectively at median 3.5 years follow up. Conclusion: Bone marrow transplantation at Marmara University Hospital has survival data in line with the tranplantation units of most Western countries. The number of transplants is expected to rise in the future provided better conditions are established for maintenance and expansion of the transplant centre.
Keywords: Allogeneic; Autologous; Bone marrow transplantation; Peripheral blood stem cell